Morphological granulometric analysis of sediment images - Balagurunathan, Yoganand (Image analysis and stereology, 2001)
Sediments are routinely analyzed in terms of the sizing characteristics of thegrains of which they are composed. Via sieving methods, the grains are separated and a weight-based size distribution constructed. Various moment parameters are computed from the size distribution and these serve as sedimentcharacteristics. This paper examines the feasibility of a fully electronic granularity analysis using digital image processing. The study usesa random model of three-dimensional grains in conjunction with the morphological method of granulometric size distributions. The random model is constructed to simulate sand, silt, and clay particle distributions. Owing to the impossibility of perfectly sifting small grains so that they do not touch,the model is used in both disjoint and non-disjoint modes, and watershedsegmentation is applied in the non-disjoint model. The image-based granulometric size distributions are transformed so that they take into account the necessity to view sediment fractions at different magnifications and in different frames. Gray-scale granulometric moments are then computed using both ordinary and reconstructive granulometries. The resulting moments are then compared to moments found from real grains in seven different sediments using standard weight-based size distributions.
Keywords: Delec, velikost; Geologic Sediments; Geološki sedimenti; Particle Size; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; Slučajnost, razporeditev; Random Allocation; geologija; geology; sedimenti; morfologija; granule; razporeditev